(untitled) (Vallis Aurea, 2024)
This work aims to investigate the possibilities of optimizing supply chains for ecological sustainability. In the tripartite components of sustainability (economy, society, environment), economic issues are currently dominating. A model of supply chains for a sustainable future should equally embrace all three components. The purpose of the work is to promote environmental sustainability. The research results are based on the mathematical method of dynamic programming. The main finding of this paper points to the conclusion that the optimization of supply chains from the point of view of total (economic and ecological) costs is the first and most important step towards greener and ecologically sustainable supply chains.